Pregnancy urinary phthalate metabolite concentrations and gestational diabetes risk factors. (November 2016) - James-Todd, Tamarra M.; Meeker, John D.; Huang, Tianyi; Hauser, Russ; Ferguson, Kelly K.; Rich-Edwards, Janet W.; McElrath, Thomas F.; Seely, Ellen W.
Abstract: Background: Epidemiologic studies suggest phthalate metabolite concentrations are associated with type 2 diabetes. GDM is a strong risk factor for type 2 diabetes. Little is known about phthalates and GDM risk factors (i.e. 1st trimester body mass index (BMI), gestational weight gain (GWG), and 2nd trimester glucose levels). Methods: A total of 350 women participating in Lifecodes pregnancy cohort (Boston, MA), delivered at term and had pregnancy urinary phthalate metabolite concentrations. Nine specific gravity-adjusted urinary phthalate metabolites were evaluated. General linear regression was used to assess associations between quartiles of phthalate metabolites and continuous 1st trimester BMI and late 2nd trimester blood glucose. Linear mixed models were used for total GWG. Multivariable logistic regression was used for phthalate concentrations and categorized GWG and impaired glucose tolerance defined as glucose ≥140 mg/dL based on a 50-gram glucose load test. Models were adjusted for potential confounders. Results: There were no associations between 1st trimester urinary phthalate metabolite concentrations and 1st trimester BMI. Mono-ethyl phthalate concentrations averaged across pregnancy were associated with a 2.17 increased odds of excessive GWG (95% CI: 0.98, 4.79). Second trimester mono-ethyl phthalate was associated with increased odds of impaired glucose tolerance (adj. OR: 7.18; 95% CI: 1.97, 26.15). A summary measure of di-2-ethylhexyl phthalate metabolite concentrations were inversely associated with impaired glucose tolerance (adj. OR: 0.25; adj. 95% CI: 0.08, 0.85). Conclusions: Higher exposure to mono-ethyl phthalate, a metabolite of the parent compound of di-ethyl phthalate, may be associated with excessive GWG and impaired glucose tolerance; higher di-2-ethylhexyl phthalate was associated with reduced odds of impaired glucose tolerance. Highlights: Higher 2nd trimester MEP concentrations were associated with a higher risk of IGT and excessive GWG Higher 2nd trimester ΣDEHP metabolite concentrations were inversely associated with continuous glucose levels in 2nd trimester No associations were found for 1st trimester urinary phthalate metabolite concentrations and GDM risk factors